Physiological Response to Speed Endurance Soccer Training in Amateur Players - I Dewa Made Aryananda Wijaya Kusuma; Nining Widyah Kusnanik; Bayu Agung Pramono; Adi Pranoto; Yanyong Phanpheng; Resti Nurpratiwi; Mokhamad Nur Bawono; Faridha Nurhayati (OVS LLC, 2024)
Objectives. This study aimed to examine the physiological response to speed endurance soccer training (SEST), which involved the measurement of heart rate (HR), blood lactate (LAC), and blood pressure (BP) are measured during the four-week intervention period. Materials and methods. The one-group pretest-posttest pre-experimental design was used in this study. The study comprised 15 male amateur soccer players with an average age of 16.13 ± 0.52 years. The participants' mean height was 167.4 ± 4.63 cm, weight was 57.69 ± 12.11 kg, and BMI was 20.44 ± 3.45 kg/m². The data findings are presented using the mean and standard deviation. The paired t-test was employed to assess the impact of each group. The threshold for statistical significance was set at a p-value of less than 0.05. The effect size (ES) was calculated using Cohen's ES as a metric to quantify the magnitude of the difference between the pretest and posttest stages. Results. The HR results monitoring during the intervention period were in the high-intensity zone, with an average of 91.67 ± 0.6 % and a HR of 187.67 ± 1.24 bpm. No significant change was observed in the heart rate response from baseline to end of intervention. The LAC results showed that the lactate level was in the high category, namely an average of 11.03 ± 1.3 mmol∙L-1. BP indicated a significant difference between pretest and posttest (p ≤ 0.05). The systolic blood pressure (SBP) demonstrated an increase of Δ % = 0.95, while the diastolic blood pressure (DBP) showed an increase of Δ % = 1.39. Conclusions. The findings of this study indicate that SEST has a notable effect on the body's physiological functions, namely on the cardiovascular system, anaerobic metabolism, and blood pressure. This effect was observed over a period of four weeks in amateur soccer players.